THEORETICAL FOUNDATIONS OF THE CORRECT ORGANIZATION OF THE COTTON HARVESTING - Tursunova Faridakhon (The Conference Hub, 2025)
The ripening of the cotton plant follows a certain pattern, as in flowering, the bolls gradually open towards the lower cone. Therefore, they do not open at once.Early ripening early pods are restrained and of good quality. In general, the quality of the main part of the cotton in the bags opened before the cold falls is at the required level. The time between the opening of the lower sac and the opening of the upper sac takes 1.5-2 months or more. As a result, the cotton crop has to be picked several times.